E-Modul Interaktif Berbasis Flipbook Terintegrasi Etnosains untuk Meningkatkan Literasi Lingkungan Peserta Didik - Aulia Azhar; Skunda Diliarosta; Fitri Arsih; Harmedi Yulian Saputra (Postgraduate, University of Mataram, 2026)
This study aimed to develop and evaluate an Ethnoscience-integrated interactive flipbook-based e-module on environmental pollution to improve junior high school students’ environmental literacy. The research employed a Research and Development approach using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation. The subjects were seventh-grade students of a public junior high school in Padang, Indonesia. Data were collected through expert validation sheets, practicality questionnaires, and environmental literacy tests. The results showed that the e-module achieved a very high validity level (0.87). Practicality testing indicated that teachers rated the e-module as very practical (88%), while students rated it as practical (79%). The lower student score was influenced by minor technical constraints, such as device limitations and internet access during implementation. Effectiveness testing was conducted using the Mann–Whitney U test, as normality and homogeneity assumptions were not fully met. The results revealed a significant difference in environmental literacy between the experimental and control groups (p < .001), with a higher mean rank in the experimental group. The improvement was further supported by a moderate effect size (d = 0.35). These findings indicate that the Ethnoscience-integrated interactive flipbook-based e-module is valid, practical, and effective in enhancing students’ environmental literacy and is suitable for contextual science learning aligned with the Merdeka Curriculum.